Validity of the test-table-test for Nordic skiing for classification of Paralympic sit-ski sports participants - Pernot, H. F. M.; Lannem, A. M.; Geers, R. P. J.; Ruijters, E. F. G.; Bloemendal, M.; Seelen, H. A. M. (Spinal Cord, 2011)
Study design: Cross-sectional study.